Pemilu Adil dan Bermartabat: Suatu Tinjauan Sistem Hukum Lawrence M. Friedman - Razak, Askari (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
The effectiveness of regulations regarding elections that are able to provide fair and appropriate sanctions in any election violations that have been committed based on the applicable legal system can determine the success of organizing transparent and accountable elections. Lawrence M. Friedman explains the elements of the legal system consist of legal structure, legal substance, and legal culture. This research is a normative legal research that uses a conceptual research approach using primary legal materials, secondary legal materials, and non-legal materials. The result of this research is that the legal structure related to general elections still has obstacles related to the efforts to process the handling of alleged election criminal violations. In terms of legal substance, Law Number 7 Year 2017 needs to explain in more detail about election crimes and the qualifications of actions taken are offenses or crimes. As well as in terms of legal culture, both election organizers, election participants and the public as voters have not fully realized the nature or purpose of general elections. So that law enforcement in general elections based on Law Number 17 of 2017 concerning General Elections has not been effective based on a review of the legal system according to Lawrence M. Friedman.